Brain-specific heterozygous loss-of-function of ATP2A2, endoplasmic reticulum Ca2+ pump responsible for Darier's disease, causes behavioral abnormalities and a hyper-dopaminergic state. Issue 18 (8th June 2021) - Nakajima, Kazuo; Ishiwata, Mizuho; Weitemier, Adam Z; Shoji, Hirotaka; Monai, Hiromu; Miyamoto, Hiroyuki; Yamakawa, Kazuhiro; Miyakawa, Tsuyoshi; McHugh, Thomas J; Kato, Tadafumi
Abstract: A report of a family of Darier's disease with mood disorders drew attention when the causative gene was identified as ATP2A2 (or SERCA2 ), which encodes a Ca 2+ pump on the endoplasmic reticulum (ER) membrane and is important for intracellular Ca 2+ signaling. Recently, it was found that loss-of-function mutations of ATP2A2 confer a risk of neuropsychiatric disorders including depression, bipolar disorder and schizophrenia. In addition, a genome-wide association study found an association between ATP2A2 and schizophrenia. However, the mechanism of how ATP2A2 contributes to vulnerability to these mental disorders is unknown. Here, we analyzed Atp2a2 heterozygous brain-specific conditional knockout (hetero cKO) mice. The ER membranes prepared from the hetero cKO mouse brain showed decreased Ca 2+ uptake activity. In Atp2a2 heterozygous neurons, decays of cytosolic Ca 2+ level were slower than control neurons after depolarization. The hetero cKO mice showed altered behavioral responses to novel environments and impairments in fear memory, suggestive of enhanced dopamine signaling. In vivo dialysis demonstrated that extracellular dopamine levels in the NAc were indeed higher in the hetero cKO mice. These results altogether indicate that the haploinsufficiency of Atp2a2 in the brain causes prolonged cytosolic Ca 2+ transients, which possibly results in enhanced dopamine signaling, a common feature of mood disorders and schizophrenia. These findings elucidate how ATP2A2 mutations causing a dermatological disease may exert their pleiotropic effects on the brain and confer a risk for mental disorders.